2010
DOI: 10.1093/brain/awq183
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal networks in children with continuous spikes and waves during slow sleep

Abstract: Epileptic encephalopathy with continuous spikes and waves during slow sleep is an age-related disorder characterized by the presence of interictal epileptiform discharges during at least >85% of sleep and cognitive deficits associated with this electroencephalography pattern. The pathophysiological mechanisms of continuous spikes and waves during slow sleep and neuropsychological deficits associated with this condition are still poorly understood. Here, we investigated the haemodynamic changes associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
135
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 94 publications
12
135
1
1
Order By: Relevance
“…26 By means of EEG-fMRI coregistration, a common bilateral BOLD increase in the perisylvian regions (plus thalamus and cingulate cortex) was observed in CSWS patients, independent of the etiology and the initial spike focus of the single cases. 12 This finding supports the notion that the involvement of these cortical regions is crucial for the neuropsychological impairment and the behavioral regression that accompany this disorder. It is then possible that the perisylvian cortex disruption represents a sort of common signature of different epileptic encephalopathies characterized by regression of acquired skills in children and adolescents.…”
Section: ] Syndromesupporting
confidence: 81%
See 1 more Smart Citation
“…26 By means of EEG-fMRI coregistration, a common bilateral BOLD increase in the perisylvian regions (plus thalamus and cingulate cortex) was observed in CSWS patients, independent of the etiology and the initial spike focus of the single cases. 12 This finding supports the notion that the involvement of these cortical regions is crucial for the neuropsychological impairment and the behavioral regression that accompany this disorder. It is then possible that the perisylvian cortex disruption represents a sort of common signature of different epileptic encephalopathies characterized by regression of acquired skills in children and adolescents.…”
Section: ] Syndromesupporting
confidence: 81%
“…EEG-fMRI studies have recently contributed to the understanding of the epileptic networks involved in different epileptic encephalopathies (EEs). To date, studies have been published in continuous spike-and-wave during sleep (CSWS), Lennox-Gastaut syndrome (LGS), and West (WS) syndromes, [11][12][13][14] revealing the existence of specific networks involved during the pathologic activity in such conditions. In [r (20)] syndrome, we recently showed that the typical theta-delta rhythm is generated within the frontoparietal cortices, suggesting a dysfunction of the premotor/sensorimotor systems.…”
mentioning
confidence: 99%
“…Independent of etiology and individual area of initial epileptic activity, patients with CSWS may be characterized by a consistent specific neuronal network of activation. In a recent study, the activation in the perisylvian/prefrontal network was associated with both activation in the thalamocortical network and deactivation in the default mode network (Siniatchkin et al, 2010). Our results and these findings suggest that children with CSWS may have abnormalities in the frontal lobe even if the epileptic focus is not frontal.…”
Section: Wwwintechopencom Sequential Prefrontal Lobe Volume Changessupporting
confidence: 71%
“…PET and SPECT studies have revealed hypermetabolism and hypoperfusion in the perisylvian region and temporo-parietal cortex associated with ESES without and with LKS (Fueki et al, 1988;Gaggero et al, 1995;Maquet et al, 2000) and lesional cases also; how unilateral perisylvian dominance with MRI and fMRI (Hegyi et al, 2009;Siniatchkin et al, (2010). The early FDG-PET study of showed that among six patients studied during the active phase of ESES, five had unilateral, focal/ regional increase of glucose metabolism in the cortex.…”
Section: Functional Imaging: Fmri and Pet Studiesmentioning
confidence: 99%
“…The thalamic nuclei remained symmetrical despite significant cortical asymmetries, suggesting either that cortico-thalamic neurons do not participate in the generation of spike-and-wave discharges or that they are inhibited by the pathologic mechanisms. Siniatchkin et al (2010) in a series of 12 patients with continuous electrical pattern simultaneously performed fMRI and EEG source analysis. They have found a common neuronal network activated during the discharges.…”
Section: Functional Imaging: Fmri and Pet Studiesmentioning
confidence: 99%